Annäherungen an das Unaussprechliche Ästhetische Erfahrung in kollektiven religiösen Praktiken - Schwaderer, Isabella; Waldner, Katharina (Religionswissenschaft, 2020)
Community and individual experiences in the fields of art and religion are often experienced and described as "inexpressible", as immediate and at the same time, as fluctuating and fleeting. They exceed the order of space and time - and yet are conditioned by the concrete ritual dimensions of the performance and execution and the sensual (aesthetic) experience. The interdisciplinary contributions of the volume are dedicated to these experiences and their representations in various media such as Dance, music and film and especially ask about transcultural dimensions. The central example is the interface between Germany and South Asia.